Student Readiness of Islamic Elementary Education for Problem-Based Flipped Learning Model in Higher Education - Priatmoko, Sigit; Sugiri, Wiku Aji; Amelia, Rizki (Journal of Integrated Elementary Education, 2025)
Innovating higher education teaching models is essential to meet the learning challenges of the 21st century. This research discusses the students' readiness and needs for the development and utilisation of the Problem-Based Flipped Learning (PBFL) model in the Islamic Elementary Education Department (PGMI) at the State Islamic University of Maulana Malik Ibrahim Malang. Using a quantitative descriptive survey method with 216 respondents from the 2022 and 2023 cohorts, the research focused on technological readiness, preference for learning styles, and perception toward PBFL. Findings indicated that the device ownership and preference of learning styles were facial in relation to visual/ self-directed, which suggested the practicality of the PBFL application. There was a moderate positive correlation between the availability of devices and readiness towards PBFL; however, limited access to the internet continues to be an obstacle. The current work adds value by incorporating Islamic principles in the design of PBFL, thereby providing a culturally sensitive framework for Islamic education. Furthermore, implementation options are developed around offline materials, student orientation programs, and institutional policies. These results could serve as a foundation for developing adaptive and creative teacher education programs that focus on educational and religious competencies, ultimately paving the way for the integration of PBFL into the PGMI curriculum in the long term.